2019
DOI: 10.1590/0047-2085000000232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de ansiedade e fatores associados em adultos

Abstract: RESUMO Objetivo Identificar a prevalência de transtornos de ansiedade em uma amostra de base populacional e fatores associados. Métodos Estudo transversal de base populacional realizado com indivíduos entre 18 e 35 anos. As variáveis sociodemográficas, índice de massa corporal, presença de doença crônica, abuso de álcool e tabagismo foram analisadas. Os transtornos de ansiedade foram verificados pela Mini Internacional Neuropsychiatric Interview 5.0. Foi utilizado o teste Qui-quadrado, considerando o inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
58

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 25 publications
2
17
0
58
Order By: Relevance
“…Obesity is a condition characterized by increase in body fat mass, causing serious harm to health. According to another study conducted in the Southern region of Brazil in 2019, 23 approximately 30% of people with anxiety disorder were obese. 23,24 In this study, positive association was found between obesity and people suffering from Prevalence of overweight and obesity in community health agents anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a condition characterized by increase in body fat mass, causing serious harm to health. According to another study conducted in the Southern region of Brazil in 2019, 23 approximately 30% of people with anxiety disorder were obese. 23,24 In this study, positive association was found between obesity and people suffering from Prevalence of overweight and obesity in community health agents anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…According to another study conducted in the Southern region of Brazil in 2019, 23 approximately 30% of people with anxiety disorder were obese. 23,24 In this study, positive association was found between obesity and people suffering from Prevalence of overweight and obesity in community health agents anxiety. However, as this study had a cross-sectional design and was conducted at a single period in time, this prevents a more in-depth analysis of this event, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalência de sintomatologia de transtorno de ansiedade generalizada e razões de prevalência bruta e ajustada de acordo com variáveis independentes -Amostra de estudantes (N = 137) de pré-vestibular de Pelotas/RS e Rio Grande/RS, 2019 Notas: % = prevalência de risco de transtorno de ansiedade generalizada por categoria; RP = razão de prevalências; IC de 95% = intervalo de confiança de 95%. 19 . Entre vestibulandos, estimou-se 23,5% apresentaram ansiedade considerada moderada ou grave, segundo a Escala Beck de Ansiedade 12 .…”
Section: Discussionunclassified
“…A saúde mental é relacionada aos fatores sociais, econômicos e culturais. O alto índice de diagnóstico de ansiedade e agravamento para TAG está relativamente ligado aos padrões comportamentais no trabalho ou ambientes que causam situações de desconforto, e fatores econômicos quando o indivíduo se depara com complicações financeiras (Costa et al, 2019).…”
Section: Fatores Intrínsecos E Extrínsecos Causadores Da Ansiedadeunclassified